Positive Postoperative Blood Cultures in Major Abdominal Surgery Patients Attending a Tertiary Hospital in Durban, South Africa - Irfaan Adam; Yoshan Moodley (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Evidence from high-income countries suggests that bloodstream infection is an essential complication following major surgery. However, studies of bloodstream infections following major surgery in lower-income settings, particularly in Africa, are rare. This study aimed to determine the incidence of postoperative bloodstream infection and to explore any association with mortality in high-risk laparotomy patients in South Africa. Methods: This study was a retrospective study, reviewing 435 consecutive adults who underwent laparotomy at a South African tertiary hospital over a five-year period. Incident postoperative bloodstream infection, defined as a positive blood culture following surgery, was determined from laboratory reports in the patient’s medical chart. Source infections and the causative microorganisms were established from laboratory reports. Inpatient mortality was determined from the patient’s hospital discharge summary. Data were summarized using descriptive statistics. Potential associations between bloodstream infection and mortality were tested using the chi-square test.Results: The incidence of postoperative bloodstream infection was 7.4%. Klebsiella pneumoniae, Escherichia coli, and Staphylococcus aureus were isolated from 21.9%, 18.7%, and 15.6% of blood cultures. Mortality in patients with bloodstream infection was 46.9% vs. 16.1% in patients without bloodstream infection (p<0.001).Conclusions: Postoperative bloodstream infection is an essential complication following major abdominal surgery with K. pneumoniae, E. coli, and S. aureus being the most common causative agents. Bloodstream infection is associated with a higher risk of postoperative mortality. Further studies are recommended to confirm the findings and improve patient management.